The C Allele in NOS3 -786 T/C Polymorphism is Associated with Elite Soccer Player’s Status - Eynon, N.; Ruiz, J. R.; Yvert, T.; Santiago, C.; Gómez-Gallego, F.; Lucia, A.; Birk, R. (International Journal of Sports Medicine, 2012)
The NOS3-786 T/C polymorphism (rs2070744) is a candidate to explain individual variations in sports related phenotypes. We determined the genotype and allele frequency of NOS3-786 T/C in a group of 60 male professional elite soccer players. Their results were compared with those of 100 world-class endurance athletes, 53 elite power athletes, and 100 sedentary, healthy men (controls) of the same Caucasian (Spanish) origin. There were significant differences in genotype frequencies between soccer players, controls, endurance and power elite athletes (all P≤0.02). These results were confirmed when we analysed allelic frequencies (all P<0.01). The likelihood of having the C allele was higher in soccer players compared with (i) controls [odds ratio (OR), 2.165, 95% confidence interval (CI): 1.362–3.441], (ii) endurance athletes (OR: 1.879, 95%CI: 1.184–2.984), and (iii) power athletes (OR: 4.032, 95%CI: 2.307–7.047). In conclusion, the -786C allele is associated with the status of being an elite soccer player, compared with non-athletic controls and also with elite endurance and power athletes. More research is needed in other groups of elite soccer players in order to replicate the results of the present study.
Keywords: genetics; athletic performance; nitric oxide synthase; polymorphism